2019
DOI: 10.3390/ijerph16142568
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Cleaning of Ultrafiltration Membrane Fouled by Humic Substances: Comparison between Hydrogen Peroxide and Sodium Hypochlorite

Abstract: Chemical cleaning is indispensable for the sustainable operation of ultrafiltration (UF) system in water and wastewater treatment. Sodium hypochlorite (NaClO) is an established cleaning agent for membranes subject to organic and microbial fouling, but concerns have been raised about the generation of toxic halogenated by-products during NaClO cleaning. Hydrogen peroxide (H2O2) is a potential “green” cleaning agent that can avoid the formation of halogenated by-products. In this work, cleaning efficacy of H2O2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 41 publications
(47 reference statements)
2
16
0
Order By: Relevance
“…Combining Figure 1, Figure 2 and Figure 3, it can be concluded that degradation of the PES membrane due to NaClO exposure was much more serious than that by H 2 O 2 exposure under the aging conditions in this work. Considering the comparable efficiency of H 2 O 2 cleaning with NaClO cleaning [18], H 2 O 2 is a better oxidative cleaning agent than NaClO because of the minimization of membrane degradation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining Figure 1, Figure 2 and Figure 3, it can be concluded that degradation of the PES membrane due to NaClO exposure was much more serious than that by H 2 O 2 exposure under the aging conditions in this work. Considering the comparable efficiency of H 2 O 2 cleaning with NaClO cleaning [18], H 2 O 2 is a better oxidative cleaning agent than NaClO because of the minimization of membrane degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is a strong oxidant with a standard reduction potential of 1.78 V, but its reactivity is restricted by a relatively high activation energy barrier [18,19]. Although its application as an oxidative cleaning agent is not as wide as that of NaClO, its effectiveness for permeability recovery has been demonstrated in several studies [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cleaning of the system included flushing with 0.1% NaOH (Merck, Darmstadt, Germany) to remove organic matter [ 71 ]. Sterilization was done by autoclaving at 121 °C for 20 min or soaking in 0.25% H 2 O 2 solution (Merck, Darmstadt, Germany), analogous to [ 71 , 72 , 73 , 74 , 75 ]. Reassembling of the skid: After cleaning and sterilization, the skid was reassembled under sterile conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Also, it is more likely that most of the pollutants that stick on the surface of the membrane were soluble to the permeate (Beyer et al 2017 ). The other method used for the sustainable operation of the membrane process is chemical cleaning of both UF and NF membranes, using different chemical agents such as sodium hypochlorite (NaClO) (Li et al 2019a ), which is effective for membrane fouling via organic wastewater treatment and microbial fouling (Malczewska and Żak 2019 ). Table 11 presents the cost analysis of protein recovery using membrane technology from different waste streams.…”
Section: Protein Recovery and Membrane Foulingmentioning
confidence: 99%